Comparison of the Clinical Efficacy of Salbutamol with Jet and Mesh Nebulizers in Asthmatic Children - Norihide Murayama; Kikuno Murayama (Pulmonary Medicine, 2018)
Background. Ultrasonic, jet, and mesh nebulizers have all been used in the treatment for asthma. Mesh nebulizers reportedly offer the best inhalation efficiency. Methods. This study aimed to clarify the utility of the mesh nebulizer, compared to jet nebulizers, in the treatment of pediatric asthma patients. Participants included 88 children <6 years old who were receiving treatment for asthma at Murayama Pediatric Clinic. Heart rate, peripheral oxygen saturation in arterial blood, and Mitsui symptom scores were compared before and after treatment with a mesh nebulizer (n=43) or jet nebulizer (n=45) using a salbutamol inhalation solution (0.2 ml for children ≧ 2 years old, n=51; 0.1 ml for children < 2 years old, n=37). Results. Other than required inhalation time, clinical findings did not differ between mesh and jet groups. In both groups, heart rate increased significantly in patients treated with 0.2 ml (1000 microg) of salbutamol. Conclusions and Clinical Relevance. The required inhalation time of the mesh nebulizer was superior to the jet nebulizer. Children ≧ 2 years with mild asthma attacks experienced a significantly increased heart rate in both groups. The dose of salbutamol (0.2 ml for ≧2 years) used for asthma attacks should be reconsidered in mild asthma.